2009
DOI: 10.1128/iai.01436-08
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Region of Difference 1 Antigen-Specific but Not Purified Protein Derivative-Specific Gamma Interferon-Secreting T Cells Correlate with the Presence of Tuberculosis Disease but Do Not Distinguish Recent from Remote Latent Infections

Abstract: The majority of individuals infected with Mycobacterium tuberculosis achieve lifelong immune containment of the bacillus. What constitutes this effective host immune response is poorly understood. We compared the frequencies of gamma interferon (IFN-␥)-secreting T cells specific for five region of difference 1 (RD1)-encoded antigens and one DosR-encoded antigen in 205 individuals either with active disease (n ‫؍‬ 167), whose immune responses had failed to contain the bacillus, or with remotely acquired latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Collectively, these results strongly indicate that antigen recognition by T cells tracks antigen profiles expressed by tubercle bacilli in association with growth phase. It is worth mentioning, however, that one study found no difference in the response to ␣-crystallin between active TB and LTBI (64). One possible explanation is that strong differences in absolute bacillary load between latent infection and multibacillary forms of active TB overcome the effect of growth-phase-associated antigen expression.…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 78%
See 1 more Smart Citation
“…Collectively, these results strongly indicate that antigen recognition by T cells tracks antigen profiles expressed by tubercle bacilli in association with growth phase. It is worth mentioning, however, that one study found no difference in the response to ␣-crystallin between active TB and LTBI (64). One possible explanation is that strong differences in absolute bacillary load between latent infection and multibacillary forms of active TB overcome the effect of growth-phase-associated antigen expression.…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 78%
“…It has been suggested that the use of particular ESAT-6-derived peptides in lieu of full-length protein may enhance discrimination between active disease and latent infection (53,56). Together with the observation that responses to ex vivo stimulation with purified protein derivative (PPD) do not differ between active TB and LTBI (64), the results obtained with ESAT-6 peptides suggest that the choice of epitope is a critical factor in the evaluation of biomarker levels in response-to-antigen assays.…”
Section: Cellular Immune Responses and Infection Statementioning
confidence: 99%
“…More concerning is the indiscriminate use of immunological assays, previously the tuberculin skin test but recently the interferon-γ release assay (IGRA), in the diagnosis of TB as a cause of PUO. The literature has been heterogeneous but in general highlights the limited sensitivity, and specificity, of IGRA for the diagnosis of active TB 20 21. All infectious diseases specialists have experience of the patient with active TB and a negative IGRA, and yet many still find themselves using the test in some patients—albeit with open eyes—its role perhaps most useful in tilting the differential in the patient without risk factors for exposure, but with granulomatous pathology or inaccessible (eg, brain) pathology on imaging.…”
Section: Diagnostic Pitfallsmentioning
confidence: 99%
“…In addition, despite a sensitivity of 80% in adults with aTB, the negative predictive value is not high enough to recommend its use to reject a diagnosis of aTB (8). The utility of these tests in adults is therefore restricted to the diagnosis of LTBI, but their sensitivities for the diagnosis of remote LTBI were recently challenged (9)(10)(11)(12)(13). As the antigens used in the commercialized gamma interferon release assays (IGRA) are poorly expressed by M. tuberculosis during its latency, corresponding antigen-specific T cells in the blood are mainly memory T lymphocytes that are not optimally detected by short-term assays (10,14).…”
Section: Latent M Tuberculosis Infection [Ltbi])mentioning
confidence: 99%